A Broad Spectrum of Liver Manifestations in Common Variable Immunodeficiency Syndrome—Two Case Reports and a Literature Overview - Eva Supovec; Jan Drnovšek (Diagnostics, 2025)
Background and Clinical Significance: Common variable immunodeficiency (CVID) is a primary B-cell immunodeficiency disorder, characterized by severe hypogammaglobulinemia and disturbed antibody production. In addition to increased susceptibility to recurrent respiratory and gastrointestinal infections, CVID can lead to a wide array of complications associated with immune dysregulation, which can also affect the liver. Liver involvement occurs in about 10% of patients with CVID, and can result from a range of causes, including infections, autoimmune disorders, lymphoproliferative conditions, granulomatous inflammation, and infiltrative processes. The most common liver manifestations include nodular regenerative hyperplasia, granulomatous or autoimmune hepatitis, and lymphocytic infiltration. The prevalence, pathophysiology, extent, and prognosis of liver involvement in CVID have not been systematically studied. Case Presentation: The object of this article is to present two patients with CVID-related liver disease and to illuminate the most relevant causes of liver involvement in CVID, describe the clinical features of their liver disease, and summarize the diagnostic and therapeutic approaches for its management. Conclusions: Liver involvement is an expected complication in patients with CVID syndrome. The delayed recognition of this pathology significantly worsens the disease prognosis, making the early detection of this potential complication crucial.